1999
DOI: 10.1095/biolreprod60.6.1483
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Administration to Superovulated Ewes Improves In Vitro Embryonic Viability1

Abstract: Retinol and its metabolites, all-trans retinoic acid and 9-cis retinoid acid, are regulators of cellular growth, differentiation, and development and have been implicated in reproductive processes including folliculogenesis and embryonic survival. Three experiments were conducted to identify effects of retinoid treatment of superovulated ewes upon subsequent in vitro embryonic development. Ewes were treated with all-trans retinol (ROH), all-trans retinoic acid (RA), 9-cis retinoic acid (CIS), or vehicle (Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
3
34
1
1
Order By: Relevance
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 55%
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 55%
“…Administration of retinol with super ovulation increased the number of transferable embryos but did not affect ovulation rate (Shaw et al, 1995). Retinol treatment in combination with super ovulation improves the developmental competence of resultant embryos (Eberhardt et al, 1999). Earlier studies have reported the presence of retinol in follicular fluid (Schweigert and Zucker, 1988;Brown et al, 2003), stating that vitamin-A concentrations to be highest in large nonatretic follicles and lowest in small atretic follicles correlated with estradiol concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that the developmental competence of the oocyte is enhanced by ROH treatment in the cow (Shaw et al 1995), sheep (Eberhardt et al 1999) and gilt (Whaley et al 1997(Whaley et al , 2000, as well as in rabbits that have high blood levels of vitamin A (Besenfelder et al 1996). In studies involving cows (Shaw et al 1995), sheep (Eberhardt et al 1999) and gilts (Whaley et al 1997(Whaley et al , 2000 the effects of retinol on follicular development were monitored and recorded 4 days post-administration.…”
Section: Introductionmentioning
confidence: 99%